Lamp as a Symbol in Theology and Iconology of Light in the Mediterranean - Tešić Radovanović, Danijela T. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Light and fire have been a part of the religious experience since the dawn of civilization, its cultic use can be traced back to as early as the Paleolithic. Seen as divine emanations, light and fire were experienced as a symbol of the divine presence. This symbolism can be observed across the Mediterranean and the Near East, from Sumerian civilization and Egypt, through Greco-Roman world until monotheistic Abrahamic religions. The cultic use of oil lamps is one of the principal means of expressing the light symbolism. These lamps were sources of light in everyday life, but also а complex cultic device, based on their function as а light provider. Being small and portable, lamps were used as compact sanctuaries, censers, altars, oil vessels, and containers of light, all in one. Due to the belief that the flame contained a gleam of astral and divine lighting, lamps had a prominent role in public and personal piety. In The Roman and late antique period, lamp makers developed various decoration schemes, based on monumental art, with religious, mythological, and everyday scenes and motifs. Lamps became objects used for creating religious identities and instruments of romanisation, and christianisation later on. The primeval symbolism of  lighting and a lamp as the embodiment of the divine presence can still be observed in Jewish synagogues  through sanctuary lamps / ner tamid, that is, through altar lamps / kandilo in the Christian churches and numerous lamps / qindīl and  lighting devices in the Muslim mosque.
Keywords: light; fire; solar cult; epiphany; lamp; iconology